Perbandingan Media Dakon dan Tangga Satuan Terhadap Pemahaman Konsep Pengukuran dalam Pembelajaran Matematika pada Siswa Kelas V SD Negeri Sekecamatan Deli Tua - Sari, Zulva; Sukmawarti, Sukmawarti (Indonesian Research Journal on Education, 2022)
This study aims to determine the comparison between dakon media and unit hands on the understanding of mathematical concepts of fifth grade elementary school students in Deli Tua District. The population in this study were all fifth grade students, totaling 448 students. While the research sample amounted to 100 students. This research is a quantitative research with the type of research is True Experimental Treatment with Pretest-Posttest Control Group Design. The instrument used is the test. From the results of the study, the average prettest score for the experimental school I was 61.4 and the prettest for the experimental school II was 55.5. then the two schools were given different treatment, so that the posttest average score for understanding the concept of the experimental school I was 86.8 and the experimental school II was 73.1. Hypothesis testing is done by t-statistic analysis. From the calculation results obtained tcount = 7.96 > ttable = 1.98 with dk = 98 and the level of significance = 0.05. It can be seen that tcount > ttable, so Ho is rejected and Ha is accepted. So the conclusion of this study is that there is a comparison of students' conceptual understanding using the Dakon media and the ladder media for the fifth grade students of SD Negeri Deli Tua.